Food Preferences and Coping Strategies among Diabetic and Nondiabetic Households Served by US Food Pantries. Issue 1 (4th March 2019) - Bomberg, Eric M; Neuhaus, John; Hake, Monica M; Engelhard, Emily M; Seligman, Hilary K
ABSTRACT: Limited access to healthy food caused by food insecurity makes diabetes mellitus (DM) self-management more challenging. Using data from Hunger in America 2014 ( n  = 60, 122 US food pantry users), we sought to understand food preferences and coping strategy utilization (e.g., choosing between paying for food and medical care) among households seeking assistance from US food pantries with and without DM members. The prevalence of wanting and not obtaining fruits, vegetables, dairy, and protein was high among all households. After adjusting for sociodemographic characteristics, households with DM members were more likely to want and not obtain fruits, vegetables, and dairy, and were also more likely to use several coping strategies to increase food access, compared to households without DM members. These results highlight the high demand for healthy food items among clients from US food pantries, particularly among households with DM, as well as the extra burden DM may place on food insecure households.